Impact of a wavy wall triangular porous cylinder on diffusive-mixed convection in a lid-driven triangular cavity - Duna T. Yaseen; Amani J. Majeed; Sahib S. Ahmed; Muneer A. Ismael (International Journal of Thermofluids, 2025)
Analyzing the double diffusive mixed convection inside a triangular enclosure with moving lid and involving a wavy porous cylinder emitting a concentration is addressed in this paper. Such a problem simulates various processes such as crystallization, absorption, and distillation where both heat and mass transfer are involved. The horizontal wall of the lid-driven cavity maintains a constant temperature, while the inclined walls of the triangle cavity are thermally insulated. The wavy wall of the inner porous cylinder releases a constant species and kept colder than the moving wall. This study presents a novel way for improving heat transmission from a surface utilizing porous cylinders. Using a porous cylinder with e porosity can improve the performance of heat transfer. The governing equations are transformed to a non-dimensional form and solved with the finite element method. The study examines how porosity (ε), Darcy number (Da), undulation number (N), and wave amplitude (A) affect fluid flow, heat transfer and concentration distribution. More improvement in the porous cylinder performance is discovered to be possible with increasing (ε), (N), (Ri), and (Re), particularly at large (Da) levels. It is discovered that the average Nusselt number rises by the porous cylinder wall's waviness. The results indicate that in certain cases, increasing N from 1 to 5 raises the Nusselt number by 6 % while increasing the Darcy number from 10−3 to 10−2 could improve convective heat transmission in the liquid by 7.5 %.